2014
DOI: 10.1371/journal.pone.0107897
|View full text |Cite
|
Sign up to set email alerts
|

A Translatable Predictor of Human Radiation Exposure

Abstract: Terrorism using radiological dirty bombs or improvised nuclear devices is recognized as a major threat to both public health and national security. In the event of a radiological or nuclear disaster, rapid and accurate biodosimetry of thousands of potentially affected individuals will be essential for effective medical management to occur. Currently, health care providers lack an accurate, high-throughput biodosimetric assay which is suitable for the triage of large numbers of radiation injury victims. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 29 publications
0
60
0
Order By: Relevance
“…In fact, Lucas et al . have shown that the murine signatures they developed are not translatable to human samples 42 . Furthermore, only two genes, including BAX , are shared by the human and murine signatures derived by Dressman et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Lucas et al . have shown that the murine signatures they developed are not translatable to human samples 42 . Furthermore, only two genes, including BAX , are shared by the human and murine signatures derived by Dressman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only two genes, including BAX , are shared by the human and murine signatures derived by Dressman et al . 42 .…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated the biological processes implicated by gene ontology analysis using DAVID. Although several groups are working towards the development of gene expression as an approach for radiation biodosimetry (69, 33, 34), such studies, as well as the development of other radiation biodosimetry methods, have focused on the classification of acute exposures. Among studies using C57BL/6 mice for acute biodosimetry development, Filiano et al .…”
Section: Discussionmentioning
confidence: 99%
“…Dose assessment in irradiated blood samples can be obtained by either using dose predictive gene or exon signatures (Paul & Amundson 2008;Kabacik et al 2011;Boldt et al 2012;Knops et al 2012;Lucas et al 2014;Macaeva et al 2016) or by monitoring the modification of transcription of single radiation-responsive genes like ferredoxin reductase (FDXR) (Manning et al 2013;Abend et al 2016).…”
Section: Introductionmentioning
confidence: 99%